Analisis Determinan Proksi Faktor yang Berhubungan dengan Kinerja Kader Posbindu Penyakit Tidak Menular (PTM) - Evodius Nasus; Ekawati Saputri (Jurnal Kesehatan, 2022)
Posbindu Non-Communicable Diseases (PTM) is a form of community participation in activities for early detection, monitoring, and early follow-up of risk factors for Non-Communicable Diseases independently, routinely, integrated, and continuously. So that the role of cadres is needed to carry out tasks in health services related to non-communicable diseases. The purpose of this study was to analyze the determinants of factor proxies consisting of training, awards, infrastructure, knowledge, and job design related to the performance of Posbindu PTM cadres in the working area of Wundulako Health Center. This study uses a descriptive-analytic design with a cross-sectional approach, sampling using a total sampling so that the number of samples is 55 people. The results of the chi-square test show that there is a significant relationship between training and the performance of Posbindu PTM cadres (p-value=0.003), there is no relationship between rewards and the performance of Posbindu PTM cadres (p-value=0.352), facilities and performance of  Posbindu PTM cadres (p-value=0.874), there knowledge and performance of posbindu PTM cadres (p-value=0.424). But, there is a significant relationship between job design and performance of Posbindu PTM cadres (p-value=0.009). This study concludes that there are only 2 factors that affect the performance of PTM posbindu cadres, i.e training and job design, so it is hoped that the Wundulako Health Center as the organizer can provide training to cadres, it must be carried out at least every month to maintain and improve cadre knowledge and socialization related to the duties and roles of cadres.